Influência da substituição de Ga por Sn nas propriedades magneto-estruturais da liga Heusler Ni2MnGa - Meza, Evel Elizabeth Lozano (2012)
We studied, in this work, magneto-structural properties of Ni50Mn25Ga25-XSnX with X = (0; 1,25; 2,5; 5; 7,5; 10; 12,5; 15; 17,5; 20; 22,5; 25) Heusler-type alloys, aiming to understand the physical origin of the martensitic phase transformation, which is presented in the ordered Ni50Mn25Ga25 Heusler compound, but absent in the Ni50Mn25Sn25 Heusler alloy. For that, we performed structural characterization of the melted and annealed alloys by X-ray diffractometry and we determined the alloys magnetic properties using DC magnetization as a function of applied magnetic field [M(H)] and temperature [M(T)] at a temperature interval from 50 to 400 K. After Rietveld analysis, we verified that all prepared samples have a single crystalline phase at room temperature, with L21- type cubic structure. The lattice parameter from the L21-type structure increase with increase of the Sn-content. In addition, from the X-ray measurements we inferred that the studied alloys have a high atomic degree order, since S-parameter, which measures this feature in Heusler-type system, is close to one (0.9 < S < 1.1). M(H) curves show a ferromagnetic behavior, but do not reach the saturation regime at 300 K for applied fields of 3 T. This observation may suggest a presence, for example, of antiferromagnetic interactions among some Mn-atoms due to the chemical disorder supported by the fact that S-quantity is not exactly equal to 1, expected when the Heusler alloy is 100% ordered. Additionally, maximum magnetizations, defined at 3 T, display first a tendency of increase and then it shows a gradual reduction (cusp-like curve) with the decrease of the valence electrons per atom (e/a). Similar behavior observed for the maximum magnetization as a function of the (e/a)-quantity, we noted for the to ferro- Abstract VI magnetic transition (TC = Curie temperature) of the L21-type phase, suggesting that the (e/a)-quantity apparently has direct influence on the Ni50Mn25Ga25-XSnX Heusler alloy magnetic properties. On the other hand, we observed, from the M(T) curves obtained at Field-cooling (FC) and Field-Heating (FH) protocols, that the temperature, where the martensitic phase transformation (TM) occurs, shifts to lower values when Sn-concentration is increased. We also noted that this structural transformation is not observed in M(T) curves, for alloys with X > 2,5. Specifically, for the Ni50Mn25Ga25 compound, TM = 233 K, while for the Ni50Mn25Ga23,75Sn1,25 Heusler-type alloy the TM value is at about 114 K. In general for our system, we concluded that TM does not scale the (e/a)-quantity, since one would expect an increase of TM values when (e/a)-quantity increases. Then, we proposed that chemical pressure, due to the small atomic radium of Ga-atoms, is responsible for the observed structural transformation in Ga-rich compounds. Finally, we have to emphasize that in alloys with martensitic transformation, there is a ferromagnetic hysteresis in austenitic L21 phase after M(T) measurements obtained in FC e FH protocols, indicating that the atomic arrangement and crystal defects of the L21-type structure of the as-prepared Ga-rich alloys are not completely reversed after the structural transformation process